Swelling around the implant body: A late complication of cochlear implantation. How to deal?. (January 2015) - Çatli, Tolgahan; Olgun, Yüksel; Çelik, Çağrı; Gur, Harun; Bayrak, Feda; Olgun, Levent
<x content-type="archive" xml:space="preserve">Abstract</x> Objective In this retrospective review, we aimed to determine the most appropriate management of the complication of late swelling around the implant body following cochlear implantation. Methods The medical records of 516 patients who underwent cochlear implantation between January 2008 and June 2013 were reviewed for a history of swelling around the implant body. Results Of the 516 patients, 16 (8 males and 8 females) had a history of swelling around the implant body following implantation. The onset of swelling was from 1 to 60 months (median 21.2 months) after implantation. Three of the 16 patients had a history of manifest trauma to the head, and the remaining 13 had experienced an upper respiratory tract infection just before the swelling arose. Discussion In the light of our clinical experiences, we may suggest that late swelling around the implant body seems associated with a manifest or hidden head trauma or upper respiratory tract infections. Conclusion After the initial assessment of swelling, surgeons should be aware of the possibility of abscess formation. As a general rule, any kind of pus collection should be drained surgically. However, in the case of pus collection without abscess formation, conservative measurements can often achieve satisfactory results.